1987
DOI: 10.2172/6690002
|View full text |Cite
|
Sign up to set email alerts
|

The spheromak as a compact fusion reactor

Abstract: After summarizing the economic and utility-based rationale for compact, higher-power-density fusion reactors, the gun-sustained spheromak concept is explored as one of a number of poloidal-field-dominated confinement configurations that might improve the prospects for economically attractive and operationally simplified fusion power plants. Using a comprehensive physics/engineering/cos ting model for the spheromak, guided by realistic engineering constraints and physics extrapolation, a range of cost-optimized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…A recently completed Spheromak reactor study 49 indicated the possibility of compact, hlgh-pover-density fusion reactors vith operationally simplified fusion pover plants.…”
Section: Spheromak Characteristicsmentioning
confidence: 99%
“…A recently completed Spheromak reactor study 49 indicated the possibility of compact, hlgh-pover-density fusion reactors vith operationally simplified fusion pover plants.…”
Section: Spheromak Characteristicsmentioning
confidence: 99%
“…However, the effects of transcrystallinity on composite properties are still unclear, and results in this area are somewhat contradictory. For example, Lee and Porter (1) suggested that transcrystallization improves transverse properties in a low fiber content AS-4/PEEK composite and Hardwich (5) concluded that crystalline structure increases general mechanical properties in glass/polypropylene systems, yet Hagenson, et al (16) showed that transcrystalline interphase does not change mechanical properties in fiber/PPS composites, and Bassell, et al (17) reported that transcrystalline morphology leads to poor interfacial bonding.…”
Section: Introductionmentioning
confidence: 99%
“…(A specific analytical solution for a toroidal flux rope embedded in a spherical shell, which is a common object of study, e.g., in laboratory plasma research and in solar physics, e.g.,Hagenson and Krakowski , 1987;Gibson and Low, 1998; Borovikov et al, 2017, etc.) …”
mentioning
confidence: 98%